2019
DOI: 10.3390/antiox8060175
|View full text |Cite
|
Sign up to set email alerts
|

BG-4 from Bitter Gourd (Momordica charantia) Differentially Affects Inflammation In Vitro and In Vivo

Abstract: BG-4 isolated from bitter gourd has been reported for anti-cancer properties. The objective was to evaluate the anti-inflammatory properties of BG-4 in vitro and in vivo. Comparative study of the anti-inflammatory properties of BG-4 in vitro and in vivo was conducted on lipopolysaccharide (LPS)-activated mouse macrophages, and on dextran sodium sulfate (DSS)-induced colitis in mice. BG-4 reduced the production of pro-inflammatory markers in LPS-activated macrophages. On the other hand, intraperitoneal administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In a study, M. charantia extracts decreased the expression of intercellular adhesion molecule and tumor suppressor (miR-221/222) in tumor necrosis-factor-alpha-treated mouse lung tissues, while reducing factors with a critical role in biological processes, such as immunity, inflammation, cell growth and survival, and development (PI3K/Akt/NF B/IB). Therefore, the administration of MC extracts prior to tumor necrosis factor alpha (TNF-α) suggests that supplementation with bitter melon might be advantageous as a chemo-preventive agent for individuals at risk of inflammatory-related diseases [85]. Another study showed that glucan endo-1,3-beta-glucosidase (BG-4), a 4 kilodaltons (kDa) peptide extracted from bitter gourd seeds using 70% ethanol, has exceedingly strong trypsin-inhibiting activity [86].…”
Section: Anti-inflammatory and Antioxidant Activitymentioning
confidence: 99%
“…In a study, M. charantia extracts decreased the expression of intercellular adhesion molecule and tumor suppressor (miR-221/222) in tumor necrosis-factor-alpha-treated mouse lung tissues, while reducing factors with a critical role in biological processes, such as immunity, inflammation, cell growth and survival, and development (PI3K/Akt/NF B/IB). Therefore, the administration of MC extracts prior to tumor necrosis factor alpha (TNF-α) suggests that supplementation with bitter melon might be advantageous as a chemo-preventive agent for individuals at risk of inflammatory-related diseases [85]. Another study showed that glucan endo-1,3-beta-glucosidase (BG-4), a 4 kilodaltons (kDa) peptide extracted from bitter gourd seeds using 70% ethanol, has exceedingly strong trypsin-inhibiting activity [86].…”
Section: Anti-inflammatory and Antioxidant Activitymentioning
confidence: 99%
“…Cell culture and treatment. RAW 264.7 murine macrophages activated with lipopolysaccharide (LPS) were used as an in vitro model of inflammation following the methods described by [19,20]. Cells were grown in DMEM media supplemented with 10% heat-inactivated FBS and 1% of penicillin/streptomycin at 37 ºC in a humidified 5% CO 2 incubator.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…67 BG-4, an active molecule extracted from bitter melon, is also a polypeptide molecule that has an anti-inflammatory effect through the NF-κB pathway. 68,69 Mass spectrometry analysis shows that it consists of four peptide chains that exerts anti-inflammatory effects primarily through reducing the nuclear translocation of NF-κB p65 subunit. 68 Besides, BG-4 can also act as an anti-tumor factor by promoting the apoptosis of intestinal cancer cells.…”
Section: Anti-tumor Peptidementioning
confidence: 99%